PENERAPAN METODE BERCERITA BERBASIS EDUKATIF UNTUK MENINGKATKAN KONSENTRASI DAN KEMAMPUAN BERBICARA ANAK KELOMPOK B TKIT UMMI DI KOTA BENGKULU - Diana Ningsih (DIADIK, 2023)
This study aims to describe the application of an educative-based storytelling method to improve concentration and speaking ability of children in group B TKIT UMMI in Bengkulu City. This research was conducted using mix method, namely Classroom Action Research (CAR) and Quasi Experimental. CAR in three cycles, each cycle consists of planning and implementation, observation and reflection, while in the Quasi Experiment with the type of one group pretest posttest.. Subjects in the CAR were the children of group B2 TKIT UMMI Bengkulu City, while the research sample in the Quasi Experiment was group B3. The data collection techniques used were observation and documentation techniques. The data analysis technique used the average test and t-test. The result of the CAR research show that the educative-based storytelling method can significantly improve concentration and speaking ability, besides that it is also proven that the educative-based storytelling method is very effective in improving speaking ability.